2015
DOI: 10.5455/ijmsph.2015.20112014125
|View full text |Cite
|
Sign up to set email alerts
|

A study of glucose-6-phosphate dehydrogenase deficiency in neonatal hyperbilirubinemia

Abstract: The G6PD deficiency increases hemoglobin vulnerability to oxidative damage, leading to hemoglobin instability and precipitation of Heinz bodies. [1] G6PD deficiency is the most common red cell enzyme abnormality associated with hemolysis. It is also known to be associated with neonatal jaundice, kernicterus, and even death. The marked elevation of bilirubin levels that sometimes occurs in the neonatal period raises the risk of kernicterus. Neonatal hyperbilirubinemia often arises in association with Gilbert's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…17 In our study, we found that about two-third of the G6PD deficient neonates with indirect hyperbilirubinemia were presented early within 24-48 h, whereas G6PD normal neonates presented late with jaundice. This is in accordance with other studies which states that though the presentation of jaundice common in 2 nd or 3 rd day but it may present as early as in first 24 h. 18 This is probably due to the ongoing hemolysis in the fetus due to perinatal stress factors in G6PD deficient babies.…”
Section: Discussionsupporting
confidence: 92%
“…17 In our study, we found that about two-third of the G6PD deficient neonates with indirect hyperbilirubinemia were presented early within 24-48 h, whereas G6PD normal neonates presented late with jaundice. This is in accordance with other studies which states that though the presentation of jaundice common in 2 nd or 3 rd day but it may present as early as in first 24 h. 18 This is probably due to the ongoing hemolysis in the fetus due to perinatal stress factors in G6PD deficient babies.…”
Section: Discussionsupporting
confidence: 92%
“…14 Male considered to be independent risk factor for NHB as the current study revealed a male:female ratio of 2.13:1, and these data are comparable to those reported from southern part of the country as shown by a study from Najaf, 15 and also to studies from other parts of the world including the China, India, and from Canada. [16][17][18] Male predominance had been contributed to their higher metabolic rate and their association with the dysfunction of the placenta. 15 Despite using expensive and sophisticated investigations, the underlying cause cannot be identified in a group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It could have been hypothesized that alterations in this part of the gene could lead to similar biochemical properties and affecting the surrounding G6P binding site. 18,19 Glucose-6-phosphate dehydrogenase -deficient persons are predisposed to the development of sepsis, complications related to sepsis after a severe injury, hepatitis, malaria, and drug intake. These are the main factors causing hemolytic crisis in G6PD-deficient children.…”
Section: Discussionmentioning
confidence: 99%